Empowering Saudi EFL Learners Using ChatGPT: An Analysis of Challenges and Educational Opportunities - Meo, Mohammad Jamshed; Alqahtani, Nasser; Albedah, Fatimah; Banu, Sameena (Forum for Linguistic Studies, 2024)
The study assessed Saudi students’ opinions, obstacles and difficulties, and the educational prospects and opportunities of ChatGPT usage in EFL classrooms. The simple random selection method was utilised to choose 235 respondents from the various stages of undergraduate programs at different colleges of two Saudi universities. A primarily self-designed questionnaire with refined items from earlier studies was sent to other groups for responses. Descriptive statistics were utilized to analyze the data quantitatively. The findings revealed that Saudi students had great excitement about ChatGPT as an important tool for language acquisition and instruction. They viewed it positively as it helped them overcome certain issues they experienced in a conventional mode of instruction. The study also found that ChatGPT usage posed certain obstacles and challenges such as inhibiting innovative and critical thinking, distorting content and quality, failing to replace EFL teachers, and failing to fully understand the social connotations embedded in idioms and phrases. It was revealed that the remarkable technological and digital infrastructure of Saudi Arabia offers substantial pedagogical and educational implications for the ChatGPT integration in Saudi EFL classes. The study suggests the incorporation of more regions and different from different disciplines to add to the study's reliability and validity.